A novel compound heterozygous mutations in protein C gene causing neonatal purpura fulminans. Issue 2 (March 2018) - Zhang, Huifei; Bi, Xiaojie; Su, Zhengxian; Tu, Xi; Wang, Lizhen; Shen, Bo
Abstract : N/A: Neonatal purpura fulminans is a rare, life-threatening disease caused by severe congenital deficiency of protein C (PC) because of homozygous or compound heterozygous mutations in the PROC gene. Mutation analysis plays a critical role in diagnosing the disorder and offering prenatal guidance. In this study, we identified a genetic defect in the PROC gene leading to neonatal purpura fulminans. The propositus had very low PC activity (4%) and PC antigen activity (5%). DNA screening of the whole PROC gene revealed two compound heterozygous mutations in exon8 (c.795_796insA) and exon9 (c.1206_1207insG). These two variation s led to the compound heterozygous mutations of Gly266Argfs * 4 and Pro405Alafs * 20, which were inherited from the patient's father and mother, respectively. His older sister is heterozygous for the Gly266Argfs * 4 mutation. The inserted nucleotides alter the protein by introducing a stop codon at the subsequent AA position, resulting in a truncated protein compared with the wild type. We deduced that the compound heterozygous mutations are responsible for the PC deficiency, the Gly266Argfs * 4 mutation has been confirmed to be a novel mutation.